Simple, self-adjustable airplane splint for axillary contractures. Issue 2 (October 2017) - Gorka, Rahul; Gupta, Ashish Kumar; Prakash, Suriya; Bakthavachel, Immanuel; Lamba, Shashank; Gohil, Amish Jayantilal
Highlights: A simple self-adjustable airplane splint for axillary burn patients. Easy and cost-effective to manufacture, using commonly available hardware. Potentially enhances the patients' ability to mobilize in the community and makes it more user-friendly. Abstract: Introduction: Axillary burns and contractures are physically debilitating. Early splintage and patient compliance is critical to improve functional outcomes. Traditional treatment of axillary contractures involved use of airplane splints which provided fixed abduction at the shoulder joint. These splints pose physical, social and environmental restrictions for the patient in crowded and narrow spaces like washrooms, buses and other means of local transport. Aims and objectives: The wearability and compliance of static airplane splints were found to be surprisingly low in such patients. Hence, to overcome these problems, we designed a modified self-adjustable airplane splint. Material and methods: The abduction support and locking mechanism with adjustable hook were fabricated using simple hardware (a cabin hook and eye arrangement-the one used commonly in windows and doors). Results and conclusion: A modification to the design of a pre-existing airplane splint has been attempted. Easy and quick manoeuvrability of the splint locking-unlocking mechanism by the user himself, along with the added advantage of possible use even in narrow crowded spaces, potentially enhances the patients' ability to mobilize in the community and makes it more user-friendly.